Determinants of Twitter adoption in local governments: empirical evidence from Italy. (2016) - Metallo, Concetta; Gesuele, Benedetta
This study aims to provide an overall picture of the use of Twitter by Italian municipalities and to investigate the determinants of Twitter adoption. We construct a synthetic indicator to measure Twitter usage by local governments. Moreover, we propose a research model to analyse the determinants of Twitter adoption. We use OLS regression modelling on 93 Italian municipalities' data during 2012. Findings show that size, financial autonomy, political position and geographical position seem to predict Twitter usage in the municipalities.